Investigations on Radiation Shielding properties of Leadaluminoborate nanocomposite. (August 2022) - Sathish, K.V.; Manjunatha, H.C.; Vidya, Y.S.; Sridhar, K.N.; Seenappa, L.; Reddy, B. Chinnappa; Raj, S. Alfred Cecil; Manjunatha, S.; Gupta, P.S. Damodara; Munirathnam, R.
Abstract: For the first time, we are reporting the analysis of X-ray/gamma ray shielding properties of Leadaluminoborate (PbAlBO4 ) nanocomposite (LABNC) synthesized by solution combustion method using mint leaves extract as a reducing agent. The nanocomposite was characterized with different techniques. The Bragg's reflections clearly indicate the formation of orthorhombic nanocomposite and (hkl) planes matches well with JCPDS card number 00-153-3962 ( P n m a ( 62 ) space group), however few less intense peaks corresponding to α Al 2 O 3 were also observed. The average crystallite size was calculated using Debye Scherrer's equation as well as W–H plot method. The surface morphology shows the particles resembling dry leaves. The EDAX pattern indicates the presence of Al, Pb, B and O elements. The direct energy band gap determined by using Wood and Tauc's relation was found to be 5.2 eV. Further, the X-ray/gamma ray shielding properties of LABNC in the energy range 0.081–1.332 MeV using NaI (Tl) detector and multi channel analyser (MCA) were measured. The measured shielding parameters are compared with the theory. Above 356 keV energy of X-ray/gamma ray, the measured shielding parameters agrees well with the theory, whereas slight deviation is observed below 356 keV. This deviation is mainly due to the influence of atomic/crystallite size of the LABNC. This LABNC finds an application as a shielding material in radiation shielding. Highlights: Radiation shielding properties of Leadaluminoborate NC (LABNC) was studied. The nanocomposite was characterized with different techniques. This LABNC finds an application as a shielding material in radiation shielding. Facile, economical, efficient, low temperature synthesis method was used.